2010
DOI: 10.1111/j.1365-2672.2010.04721.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole cell protein profiling reiterate phylogenetic relationships among strains of Yersinia enterocolitica biovar 1A as discerned earlier by different genotyping methods

Abstract: Aim:  To evaluate whole cell protein profiling vis‐à‐vis genotyping to discern phylogenetic relationships among strains of Y. enterocolitica biovar 1A. Methods and Results:  Whole cell protein profiling of Y. enterocolitica biovar 1A strains was performed using SDS–PAGE. Twenty‐one distinct protein profile types were obtained among a collection of 81 strains isolated from clinical and nonclinical sources. Whole cell protein profiling exhibited discriminatory index (DI) of 0·80 and clustered the strains into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Moreover, the presence of the gene hreP was correlated with the presence of ystB . Our study corroborates with studies where B1A strains isolated from India, USA, French, Germany and Finland were divided into clusters that differed in the frequency of some virulence markers .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the presence of the gene hreP was correlated with the presence of ystB . Our study corroborates with studies where B1A strains isolated from India, USA, French, Germany and Finland were divided into clusters that differed in the frequency of some virulence markers .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, these studies showed that the presence of certain virulence genes was related to a specific cluster and not to the clinical or non‐clinical sources of isolation. These studies were conducted with strains isolated mainly from India, Finland, as well as, a few strains isolated in France, Germany and the United States .…”
mentioning
confidence: 99%
“…Two major clonal groups of Y. enterocolitica 1A have been reported earlier by different genotypic and phenotypic methods [10,11,17,22]. Furthermore, Bhagat and Virdi have shown a correlation between the distribution of virulence-associated genes myfA, ystB and 10 hreP and the clonal groups [3].…”
Section: Discussionmentioning
confidence: 80%